Development of Web Application for University of Uyo Post UTME Examination Timetable - Johnson, Enyenihi Henry; Rosemary, Ngwu Chinyere; Dan, Eduediuyai (Review of Computer Engineering Research, 2019)
In this paper a web application for Post Unified Tertiary Matriculation Examination (Post UTME) timetable for University of Uyo (UNIUYO) was presented. The system includes a web-based mapping system for visualizing the Post UTME examination venues on a Google base map. The system interfaces with the Google map server using a comma separated version interface file that contains the spatial data of the items to be visualized on the Google base map. An evolutionary software development model was used in the development of the web application. The system was implementation using Macromedia Dreamweaver, Cascaded Style Sheet (CSS), MYSQL Database Management System, HTML language, PHP server-side scripting language, Apache web server and Google Maps application programming interface. The application was hosted locally and sample Post UTME examination timetable data from UNIUYO were used to demonstrate the effectiveness of the Post UTME timetable web application.